Penerapan Manajemen Mutu Dalam Meningkatkan Kualitas Pelayanan Kesehatan - Rini Herdiani; Sunirah Sunirah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The quality of health services is a key indicator in assessing the performance of health care facilities. One strategic approach used to improve service quality is the implementation of quality management. This study aims to analyze the implementation of quality management in improving the quality of health services and its impact on patient satisfaction. The research method used was descriptive analytical research with a cross-sectional approach. The study sample consisted of health workers and patients at health care facility X. Data were collected through questionnaires and observations, then analyzed univariately and bivariately. The results showed that the implementation of good quality management, including quality planning, quality control, and continuous quality improvement, was significantly associated with improved health care quality. The conclusion of this study is that quality management plays a crucial role in improving service quality and patient satisfaction, and therefore needs to be implemented consistently and sustainably.